ANTIBODY PRODUCTION IN VITRO : I. SINGLE CELL STUDIES OF THE SECONDARY RESPONSE TO SHEEP ERYTHROCYTES - Harris, Gilmour (The Rockefeller University Press, 1968)
The effect of high specific activity thymidme-(3)H on proliferation and antibody production, using the hemolytic plaque-forming technique, by spleen cell suspensions in vitro from rabbits killed after a boost of SRC's has been studied. High specific activity thymidine-(3)H inhibited the proliferative ay well as the antibody response to antigen, and it was conduded that this was the result of the incorporation of radioactive (3)H into the nuclei of dividing cells which were synthesizing antibody in these cultures. The stimulation of the rate of DNA synthesis by specific antigen could be correlated with the ability of antigen to maintain antibody production, as measured by the specific hemolytic plaque-forming technique, above levels found in control cultures, incubated without antigen. Radioautographic studies of PFC's in vitro showed that the majority of the cells arose from the DNA-synthesizing population of cells in these cultures, confirming the conclusions from the results of the inhibitory effects of high specific-activity thymidine-(3)H on PFC's. It was found that these PFC's, labeling with thymidine-(14)C, formed only a small proportion of all the cells labeled in this way in these cultures. The postulation was made that antigen, in vitro, provided a stimulation for cell proliferation in the responsive population of rabbit spleen cells, but that only a small proportion of this population could be induced by antigen to synthesize antibody.